CHICK QUALITY OF HUBBARD BROILER BREEDERS TRAIN WITH THREE DIFFERENT EGG WEIGHTS AND STORAGE PERIODS AT FOUR PRODUCTION PHASES - H. M. Ishaq; M. Akram; M. E. Baber; A. S. Jatoi; A. W. Sahota; K. Javed; M. H. Jaspal; S. Mehmood; J. Hussain; F. Hussnain (Journal of Animal and Plant Sciences, 2015)
The present study was conducted at a commercial hatchery with the objective to evaluate the chick quality (average day-old chick weight, chick to egg ratio, A+ Chicks, A, US and B grade chicks) from fertile eggs of Hubbard broiler breeder strain during four production phases, categorized into 3 egg weights and 3 different storage periods maintained at. For this purpose, eggs during 4 production phases (pre-peak; 25-28, peak; 29-36, post-peak; 37-52 and terminal; 53-56th weeks of age) were categorized into three different weight categories (small, medium and large; subject to change in each production phase), stored for three different durations (1, 4 and 7-days) and replicated 6 times. A total of 93312 fertile eggs; pre-peak: 11664, peak: 23328, post-peak: 46656 and terminal: 11664 eggs in 4 production phases were collected. During each week of the experiment, a total number of 972 eggs per storage period from three egg weight categories replicated 6 times (each replicate containing 54 eggs) were  incubated in a commercial hatchery. The data were analyzed by ANOVA technique under randomized complete block design in 4×3×3 factorial arrangement and means were compared by using DMR Test. The results of the present study showed that the egg weight categories and length of storage period  significantly (p<0.05) influenced the average chick weight, chick to egg ratio, A+ chick’s ‘A’ grade chick’s  US chick’s and ‘B’ grade chicks percent. The highest average chick weight, chick to egg ratio, A+ chick’s  and ‘A’ grade chick’s percent was observed in large egg weight category followed by those in medium and small ones in all the production phases, while, the highest ‘US’ and ‘B’ grade chick’s percent was observed in small egg weight category in all production phases. Higher average chick weight, chick to egg ratio and US chick percent were observed in one and four day’s storage than that of seven days storage in all the production phases. Higher A+ chick percent in one and four days storage was observed than that of seven days in peak and post-peak, while, higher ‘A’ grade chick percent was recorded in one and four days storage than that of seven days in pre-peak and peak.
Keywords: Broiler breeder strain; average chick weight; chick grade; chick to egg ratio; production phase